2017
DOI: 10.1021/acs.biomac.7b00860
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Upper Critical Solution Temperatures for Acrylamide Copolymers with Bile Acid Pendants

Abstract: Acrylamide derivatives of bile acids are chosen as a hydrophobic comonomer to copolymerize with acrylamide via reversible addition and fragmentation chain transfer (RAFT) polymerization to afford a series of copolymers of P(AAm-co-CAA). These copolymers exhibit a sharp and reversible insoluble-soluble transition in water upon heating to a mixing temperature (T) related to the upper critical solution temperature (UCST). T of these copolymers can be conveniently tuned to a practical temperature range, around 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…For the latter, it would be of interest to synthesize it from vinyl monomers instead of modifying a pre-existing polymer and comparing the two synthetic routes in terms of UCST tuning. Poly(acrylamide-co-cholic acid acrylamide), P(AAm-co-CAA), was copolymerized from a modified acrylamide monomer and yielded a copolymer exhibiting a concentration dependent UCST: 48 °C at 10 mg/mL down to 24 °C at 1 mg/mL in water [123]. Rather than having a copolymer, Seuring and Agarwal also showed that polymethacrylamide (PMAAm) has a UCST in water but only reported one example with the critical temperature at 57 °C at 10 mg/mL with a broad hysteresis [114].…”
Section: Iii12 P(aam-co-an) and Other Acrylamide Copolymersmentioning
confidence: 99%
“…For the latter, it would be of interest to synthesize it from vinyl monomers instead of modifying a pre-existing polymer and comparing the two synthetic routes in terms of UCST tuning. Poly(acrylamide-co-cholic acid acrylamide), P(AAm-co-CAA), was copolymerized from a modified acrylamide monomer and yielded a copolymer exhibiting a concentration dependent UCST: 48 °C at 10 mg/mL down to 24 °C at 1 mg/mL in water [123]. Rather than having a copolymer, Seuring and Agarwal also showed that polymethacrylamide (PMAAm) has a UCST in water but only reported one example with the critical temperature at 57 °C at 10 mg/mL with a broad hysteresis [114].…”
Section: Iii12 P(aam-co-an) and Other Acrylamide Copolymersmentioning
confidence: 99%
“…The three steps, however, were carried out in three different solvents, so the procedure was not one‐pot. UCST‐type responsive copolymers were obtained by RAFT polymerization of monomers functionalized with bile acid, 92 zwitterionic sulfobetaines, nitrile, diacetone acrylamide 93 . Multiple hydrogen bond forming monomers were polymerized using a PEG‐based CTA to obtain double hydrophilic block copolymers affording core‐stabilized, thermoresponsive micelles 94 .…”
Section: Background: Matching Building Block Studs For Specific Compositions Architectures and Functionsmentioning
confidence: 99%
“…Tpt of this copolymer can be easily tuned between 5 to 85°C by varying the molar fraction of bile acid monomer in the copolymers. Further, authors also demonstrate that the UCST of copolymer could also be controlled by using β-cyclodextrin (β-CD) as an additive in water [36]. Käfer et al [4] utilized poly(ethylene glycol) (PEG, M n2 000 g/mol) as a macro-azoinitiator to impart dual thermoresponsive property in P(AAm-co-AN) copolymer.…”
Section: Poly(acrylamide-co-acrylonitrile)mentioning
confidence: 99%
“…(CMDT -cyanomethyl dodecyl trithiocarbonate, AIBN -2,2′-Azoisobutyronitrile). Reproduced with permission from[36], Copyright © 2017 American Chemical Society.…”
mentioning
confidence: 99%